PENGARUH PEMUPUKAN KALIUM TERHADAP KELAKUAN STOMATA DAN KETAHANAN KEKERINGAN - Jasmi Jasmi (Jurnal Agrotek Lestari, 2018)
This study aims to know the effect of the nutrient potassium to stomatal opening and drought resistance. The design used in this study is a randomized block design (RAK) 3x2 factorial repeated 4 times to harvest I and II. Factor 1 (K): KCl 0, 50, 100 kg / ha. Factor 2: enough water (air conditioning), water less (AK). Dose of fertilizer: Urea 200 kg / ha and KCl according to treatment-given 2 times, SP-36 100 kg/ha at planting. Observations were in leaf area, protein content, the width of stomata, net assimilation rate (LAB), relative growth rate (LPN), and the ratio of leaf area (NLD). Net assimilation rate was not significantly different among all treatments. The results showed that the harvest II occurred a real difference to the given leaf area with no water, but potash fertilizer was not significantly different. Net assimilation rate was not significantly different among all treatments. Water shortage conditions give real effect to the width of stomata in comparison to other treatments. Provision of adequate water is a significant real influence on the content of proline. There is no interaction between the provision of water and potassium fertilizer to the total dry weight of the harvest 2 at treatment K1A1 (K50 and less water) was lower than treatment K2A2 (K100 and enough water).Keywords: corn, drought resilience, potassium fertilizers, stomata